PENGARUH LITERASI KEUANGAN, KEMUDAHAN, DAN KEAMANAN TERHADAP KEPUTUSAN BERTRANSAKSI MENGGUNAKAN QRIS PADA UMKM DI BSI UMKM CENTER ACEH: Pengaruh Literasi Keuangan, Kemudahan, Dan Keamanan Terhadap Keputusan Bertransaksi Menggunakan Qris Pada UMKM Di Bsi UMKM Center Aceh - Alfi Syahrin; Marlizar; Sulfitra (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
This study aims to analyze the influence of financial literacy, ease of use, and security on the decision to transact using QRIS among MSMEs (Micro, Small, and Medium Enterprises) at the BSI MSME Center in Aceh, both partially and simultaneously. The research employs a quantitative approach with descriptive and causal methods. Data were collected through questionnaires distributed to 84 MSME respondents at the BSI MSME Center in Aceh, selected using purposive sampling techniques. Data analysis includes validity and reliability tests, multiple linear regression analysis, and partial and simultaneous hypothesis testing. The results reveal that financial literacy does not have a significant partial effect on the decision to transact using QRIS, while ease of use has a positive and significant partial effect. Security also does not significantly influence the decision to transact. However, simultaneously, financial literacy, ease of use, and security significantly influence the decision to transact using QRIS. The implications of this study highlight the importance of enhancing the ease of use of QRIS through interface simplification and user training, as well as strengthening financial literacy and security to support the adoption of digital payment technologies among MSMEs. These findings can serve as a reference for Bank Syariah Indonesia, the government, and payment service providers in designing educational programs and technological advancements to promote QRIS usage in the MSME sector.